UMUR IBU DAN PARITAS SEBAGAI FAKTOR RESIKO KELAHIRAN PREMATUR DI PUSKESMAS MANDIRAJA 1 KABUPATEN BANJARNEGARA - Dewie Sulistyorini; Lia Aria Ratmawati (Jurnal Ilmiah Medsains, 2020)
Infant Mortality Rate (IMR) is calculated from the number of infant deaths 0 <12 months per 1000 live births in an area in one year. The Infant Mortality Rate (IMR) in Banjarnegara Regency in 2018 was 14.1 / 1000 live births, which in absolute terms was calculated from the number of infant deaths of 216 with live births of 15,317. The Infant Mortality Rate (IMR) in 2018 increased compared to 2017 which was only 13.37 / 1000 live births with the number of deaths of 204 cases from 15,255 live births. One of the important obstacles for the progress of MDGs 4 so that it fails to reduce infant mortality, namely death from a single cause, prematurity. Preterm labor is a dangerous thing because of the potential to increase perinatal mortality by about 65% -75%, generally associated with low infant weight weighing less than 2,500 grams. Several factors have contributed to the occurrence of preterm labor such as factors in the mother, fetal and placental factors, or other factors such as socioeconomic. The research objective was to determine the picture of maternal age and parity as risk factors for preterm birth. The basic method of research used in this research is descriptive analysis research method by looking at the mother's age as a risk of preterm birth. The sampling technique was carried out by the total sampling method, namely taking all samples from the total population. The data collection method in this study was carried out through secondary data, namely taking medical records. The results showed that most of the respondents 90.3% (37 people) were in the low risk age category (20-35 years), and there were 9.7% (4 people) in the high risk age category (<20 and> 35 years). More than half of maternal parity was in the low risk category, namely 22 respondents (53.7%) and the other part, namely 19 respondents (46.3%), which were in the high risk category.